Resíduos da construção civil em Araguari-MG : do diagnóstico à proposta de um modelo gerencial proativo - Marques, Rogério Borges (2007)
Recent surveys carried out in several Brazilian cities show that Construction and Demolition Waste RCD represent, in some cases, more than 50% of the mass of the urban solid residues. The municipal administrations have been having difficulties to manage in an effective way the great amounts of RCD and to solve the problem of the irregular deposit that harm the population s quality of life and cause serious social, environmental and sanitary problems. This work made a diagnosis of RCD situation in Araguari, with the objective of supplying subsidies to the Municipal Public Administration for the elaboration of the Integrated Plan of Civil Construction Residues Management, as foreseen in the Resolution no. 307 of the National Environment Council. The bibliographical and documental researches provided the current situation of the theme. The surveys involved interviews with application of questionnaires and informal interviews and the field work involved exploratory visits, direct observations, photographic registrations and the mapping of the deposit areas of RCD. The obtained data were then organized in tables, graphs and maps. The estimate of the RCD volume generated in the city was done based on the registration of the number of deposit made by the transport agents in the local landfill, about 4314 m³/monthly. The visual and qualitative characterization made it possible to evaluate the reuse and recycling potential and served as a subsidy for the proposition of a management model that aims to contribute to solving the RCD problem in the city.